The girl who knew too much [large type] - Quick, Amanda (Quick, Amanda. Burning Cove, California, 2017)
When Hollywood moguls and stars want privacy, they head to an idyllic small town on the coast, where the exclusive Burning Cove Hotel caters to their every need. It's where reporter Irene Glasson finds herself staring down at a beautiful actress at the bottom of a pool. The dead woman had a red-hot secret about up-and-coming leading man Nick Tremayne, a scoop that Irene couldn't resist--especially since she's just a rookie at a third-rate gossip rag. But now Irene's investigation into the drowning threatens to tear down the wall of illusion that is so deftly built around the famous actor, and there are powerful men willing to do anything to protect their investment. Seeking the truth, Irene finds herself drawn to a master of deception. Oliver Ward was once a world-famous magician--until he was mysteriously injured during his last performance. Now the owner of the Burning Cove Hotel, he can't let scandal threaten his livelihood, even if it means trusting Irene, a woman who seems to have appeared in Los Angeles out of nowhere four months ago. With Oliver's help, Irene soon learns that the glamorous paradise of Burning Cove hides dark and dangerous secrets. And that the past--always just out of sight--could drag them both under.